2019
DOI: 10.1007/s00018-019-03365-1
|View full text |Cite
|
Sign up to set email alerts
|

Structural basis of homologous recombination

Abstract: Homologous recombination (HR) is a pathway to faithfully repair DNA double-strand breaks (DSBs). At the core of this pathway is a DNA recombinase, which, as a nucleoprotein filament on ssDNA, pairs with homologous DNA as a template to repair the damaged site. In eukaryotes Rad51 is the recombinase capable of carrying out essential steps including strand invasion, homology search on the sister chromatid and strand exchange. Importantly, a tightly regulated process involving many protein factors has evolved to e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
73
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 99 publications
(84 citation statements)
references
References 172 publications
0
73
0
1
Order By: Relevance
“…We found 1352 transcripts upregulated in e2f5 mutants compared to wild-type, whereas 763 transcripts were downregulated (FDR< = 0.05). Surprisingly, most genes associated with homologous recombination, including rad51, blm, ino80 and brca2 [37,38], showed grossly normal expression levels in the mutants (Fig 3B, S2A Fig). However, the expression of dmc1, an essential gene involved in meiosis homologous recombination, was significantly downregulated in the mutants (Fig 3B, S2A Fig).…”
Section: Transcriptome Analysis Of E2f5 Mutantsmentioning
confidence: 97%
“…We found 1352 transcripts upregulated in e2f5 mutants compared to wild-type, whereas 763 transcripts were downregulated (FDR< = 0.05). Surprisingly, most genes associated with homologous recombination, including rad51, blm, ino80 and brca2 [37,38], showed grossly normal expression levels in the mutants (Fig 3B, S2A Fig). However, the expression of dmc1, an essential gene involved in meiosis homologous recombination, was significantly downregulated in the mutants (Fig 3B, S2A Fig).…”
Section: Transcriptome Analysis Of E2f5 Mutantsmentioning
confidence: 97%
“…The L93-5 HL 647 oligonucleotide (5 HiLyte TM Fluor 647-AAA-GGC-GGT-AAT-ACG-GTT-ATC -CAC-AGA-ATC-AGG-GGA-TAA-CGC-AGG-AAA-GAA-CAT-GTG-AGC-AAA-AGG-CCA-GCA -AAA-GGC-CAG-GAA-CCG-TAA-AAA-3 [26,56] was obtained from Eurogentec (Liege, Belgium). This oligonucleotide is 100% homologous to pUC19 region 2523-2615.…”
Section: Circular D-loopmentioning
confidence: 99%
“…After that, the recombinase performs a homology search to find a dsDNA having homologous sequence. The global mechanism is reviewed in [12,56,58]. Briefly, the homology recognition and short strand exchange require binding of ATP, allowing filaments to function as rotary motors.…”
Section: Rada Catalyzes D-loop Formation On a Circular Dna Substratementioning
confidence: 99%
See 1 more Smart Citation
“…We recently demonstrated that the semi-hydrophobic environment created by ethylene glycol ethers, such as poly-ethylene glycol (PEG), significantly weakens DNA base-stacking strength but not the hydrogen bonding, and also promotes the DNA strand-exchange reaction even in the absence of any recombinase protein (Feng et al, 2019). Interestingly, both RecA and Rad51 elongate DNA by unstacking one base pair of every three, evidencing a weakening of the base-stacking forces (Chen et al, 2008;Xu et al, 2017;Sun et al 2020). Interestingly, we also note that several hydrophobic residues are present in the proximity of the DNA-binding sites of both Rad51 and RecA (the so-called L1 and L2 loops), and, thus, we speculate that these, just like PEG, can provide a hydrophobic environment that may catalyse the strandexchange reaction.…”
Section: Contributions Of Other Factors Than Hydrogen Bonds To Dna Bamentioning
confidence: 99%